Syndrome of inappropriate antidiuresis secondary to multiple myeloma: a case report and literature review - Fan, Linling; Ding, Ting; Mao, Liya; Wang, Qian; Ye, Hongying; Li, Yiming; Zhang, Shuo; Ji, Lijin (Frontiers in Oncology, 2026)
The syndrome of inappropriate antidiuresis (SIAD) has been associated with various diseases. However, to our knowledge, only a few studies have reported multiple myeloma (MM) as a potential cause of SIAD. We report a case where hyponatremia served as the primary clinical manifestation, diagnosed with SIAD and subsequently confirmed as multiple myeloma. Following anti-myeloma therapy, the hyponatremia was successfully corrected upon achieving a hematologic response classified as Very Good Partial Response (VGPR). This case contributes to an uncommon etiology of SIAD, highlighting the potential association between SIAD and multiple myeloma, and underscores the need for further research into this connection.